Computerized Neuropsychological Assessment in 6–9 Years-old Children - Korneev, A; Akhutina, T; Gusev, A; Kremlev, A; Matveeva, E (KnE Life Sciences, 2018)
The article presents a new computer-based test battery of neuropsychological assessment in 6–9-year-old children. The battery consists of seven tests for assessing executive functions, functions of activation regulation, functions of visual-spatial information and auditory information processing. The following tests are described in the article: the Dots task, two-colored Schulte–Gorbov tables, Corsi block span test and Understanding of Similar Sounding Words test. The battery is developed in the software platform ‘MSU-Practice’ (http://psychosoft.ru). The system allows researchers to conduct the tests, collect data and analyze them. In addition, it includes cloud service to support the collaboration of different research groups. A total of 21 preschoolers, 52 first-graders and 114 second-graders took part in a pilot study. All three groups of children took the four computer tests and went through a neuropsychological assessment adapted for children between the ages of 5 and 9. The correlation analysis showed consistency between the results of the computer tests and the results of the neuropsychological assessments. This allowed us to conclude that the new computer methodology is sufficiently sensible and valid to assess different components of higher mental functions in children. Keywords: neuropsychology, higher mental functions, primary school children, cognitive functions, computer-based tests